Regulating Court Jurisdiction to Protect Weaker Parties: An Overview of the Indonesian Civil Justice System - Sujayadi, Sujayadi; Wijayanta, Tata; Herliana (Yuridika, 2023)
It is necessary to facilitate an easy access to the courts to protect weaker parties. This can be achieved by regulating the personal jurisdiction of the court, so that weaker parties can easily access the courts. In Indonesian civil justice system, some regulations have been implemented to protect weaker parties through the jurisdiction of the courts. This article will elaborate those regulations and their obstacles in protecting the access of consumers, workers, women and children, and foreigners to the Indonesian courts. Statutory approach with reference to the general principles of the court personal jurisdiction and the principles of access to justice for the weaker parties will be employed. This article finds that some regulations related to the court personal jurisdiction in Indonesia provide protection to the weaker parties by allowing them to submit their claim to the court where they reside against the counterparty. However, lack of consistency may hinder the implementation.